Exploring viral diversity in diarrheic porcine feces: a metagenomic analysis from an Indian swine farm - Maan, Sushila; Batra, Kanisht; Rajendhran, Jeyaprakash; Joseph, Raison; Singh, Vikash K.; Chaudhary, Deepika; Sindhu, Swati; Kadian, Vijay; Kumar, Aman; Maan, Narender Singh; Mor, Sunil (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPig husbandry is a vital sector in India, providing nutritional security and employment for marginalized communities. Pigs are advantageous due to high reproduction rates and fecundity, shorter generation intervals, and efficient feed conversion, requiring minimal housing. However, the swine industry encounters significant disease challenges, particularly viral gastroenteritis, which poses serious public health risks, especially in developing countries. Pigs serve as natural reservoirs and amplifiers for numerous viruses with zoonotic potential, making disease surveillance essential.MaterialsIn this study, we conducted a metagenomic analysis of 15 fecal samples from diarrheic pigs on a farm in India, marking the first exploration of the fecal virome diversity in this region. Our next-generation sequencing approach has enabled the unbiased detection of multiple viral agents in the porcine fecal samples, detecting both known and novel viral agents without prior target knowledge.ResultsThe key and novel viruses obtained in our study were porcine circovirus, porcine parvovirus 7, porcine mamastrovirus 3, porcine sapelovirus A, and porcine enterovirus G. This work resulted in the generation of full genomes for multiple porcine viruses, including Circovirus, Enterovirus, Sapelovirus, and Mamastrovirus, along with partial genomes of Parvovirus, Picobirnavirus, Porcine stool-associated RNA virus (Porcine Posavirus), Kobuvirus, and Rotavirus, all subjected to phylogenetic analysis.ConclusionOur survey indicates frequent co-infections with diverse viruses, creating conducive environments for viral recombination and reassortment. Continuous surveillance of viral pathogens in animal populations is essential for understanding the dynamics of both known and novel viruses and for detecting emerging pathogens, along with their zoonotic and pathogenic potential.